Examining The Effects of The Mahatma Gandhi National Rural Employment Guarantee Act (Mgnrega) On the Lungei Municipal Council Region: An Analysis - Lalremthanga, R; Lalremtluanga, Rotluangpuia; Rosangpuii, Rosangpuii; Lalchhuanawma, MC (Journal of Neonatal Surgery, 2025)
Lunglei Municipal Council (LMC) is an unprecedented administrative stratum envisioned to be established within the Lunglei District and has been in embryonic form since its establishment. LMC has been an essential administration link since its origin, and planning has been undertaken to initiate the ultimate development confined to its area. Along with the introduction of LMC, Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA), the wage employment programme initiated by the union government, encountered an abrupt termination within LMC. Therefore, the status of MGNREGA within the LMC is of great concern. Many records and data related to the programme implemented in Mizoram exist, yet the specified area of LMC is labelled as new and remains untouched. The study highlights how MGNREGA has been terminated and the impacts of the operation. Primary and secondary data were gathered. Face-to-face interviews with the local council chairman from different localities are also held, which paves the way for a decisive study